2004
DOI: 10.1128/cdli.11.3.618-620.2004
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Commercial Immunoassays for Detection of Antibody against Helicobacter pylori in Thai Dyspeptic Patients

Abstract: The performance of five immunoassays for detection of immunoglobulin G antibody against Helicobacter pylori in 191 dyspeptic patients was evaluated. The sensitivities, specificities, accuracies, positive predictive values, and negative predictive values ranged from 86.32 to 97.89%, 57.95 to 72.22%, 77.02 to 83.76%, 71.54 to 77.42%, and 83.33 to 96.23%, respectively. The immunoglobulin A test kit also gave a high sensitivity and negative predictive value (95.79 and 91.40%, respectively), while the specificity w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 13 publications
1
9
0
Order By: Relevance
“…The performance of an earlier version of this kit was reported to be less than optimal with a Chinese population [7]. However, the current version of the kit showed the same high degree of sensitivity with Thai dyspeptic patients [18] as found in the present study. In the Thai study, all the kits tested had a low specificity, but these determinations suffered from the difficulties entailed when trying to identify true‐negatives, especially in an Asian setting.…”
Section: Discussionsupporting
confidence: 60%
“…The performance of an earlier version of this kit was reported to be less than optimal with a Chinese population [7]. However, the current version of the kit showed the same high degree of sensitivity with Thai dyspeptic patients [18] as found in the present study. In the Thai study, all the kits tested had a low specificity, but these determinations suffered from the difficulties entailed when trying to identify true‐negatives, especially in an Asian setting.…”
Section: Discussionsupporting
confidence: 60%
“…19 This trend could also have arisen from possible strain cross-reactivities, sampling errors, differences in defi ning the cut-off values or denial of some patients with normal endoscopy or recent consumption of drugs. [1,19,20] Interestingly, we found no signifi cant difference in the quantity of antibody in either serum or saliva between the normals and those with gastritis or duodenal ulcers [ Figure 3] but a signifi cant difference in the prevalence of these antibodies was observed between the normal group and patients with DU (P = 0.0001 and 0.0015 for serum and saliva, respectively). This supports the usefulness of these tests in detecting HP-associated DU patients and contrasts previous fi ndings which suggested that serum IgG assays were much better than saliva IgG in detecting such patients.…”
Section: Discussionmentioning
confidence: 53%
“…[15] The present study compared the performance of serum and saliva HP-specifi c IgG serology to antral biopsy histopathology, which is considered one of the gold standard methods for HP detection in a population with high prevalence of HP infection. [1,16] The performance of both serum and saliva immunoassays were concordant with the detection of HP in biopsies from patients with DU and approaches the fi ndings in patients with gastritis. These results are similar to previous reports, which also documented the good sensitivity and specifi city of these assays, [6,17] but a recent report from Canada demonstrated a low sensitivity and specifi city of the saliva ELISA test.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…The most frequent used diagnostic laboratory techniques are culture, stained smears, urease test, PCR assay, Western immunoblotting and histopathological examination of biopsy specimens [10,11]. However, these methods necessitate obtained gastric biopsy materials by an endoscopic invasive procedure [12]. Besides, cultural methods are time-consuming and show low sensitivity [11].…”
Section: Open Access Research Articlementioning
confidence: 99%